Analisis Kepuasan Nasabah Terhadap Kualitas Pelayanan Di P.T. Pegadaian Syariah Cabang A. Yani Pontianak - Selfy Fajriani (JURNAL MANAJEMEN MOTIVASI, 2015)
This study wanted to see customer satisfaction with quality of services provided by the Syariah Branch P.T.Pegadaian A.Yani Pontianak. The research uses a descriptive approach, the data obtained through interviews, observations, and questionnaires. Population is taken from Ar-Rum customers and Mulya, samples were selected purposively up to 100 people. The analyzer is used to compare the level of importance and performance. Research results revealed that customers were not satisfied, which can be seen in the larger impotance of the performance.